PENGARUH CELEBRITY ENDORSER, ASOSIASI MEREK, KEPERIBADAIAN MEREK DAN KARAKTERISTIK PRODUK TERHADAP INTENS PEMBELIAN PRODUK KOPI DI JAKARTA BARAT - Kurniati W Andani, Hannes Widjaya, Chandra Saputra, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2015)
Perceptions of the product can be built the company by providing information on the product, and the best way in the delivery of information is the promotion. One way of promotion of the most rising concern of many companies in introducing their products is through advertising. The purpose of this study was to determine the influence of celebrity endorsers, brand association, brand personalities and characteristics of the product to the intention of purchase. Sample selection methods by using a simple random sampling. Data obtained through questionnaires of 125 respondents in West Jakarta as a sample of researchers. Analyses were performed using multiple regression analysis. The results showed that of the four independent variables, celebrity endorser, brand association, brand personality and product characteristics significantly influence purchase intention simultaneously, while celebrity endorser does not significantly affect the intense partial purchase.